ANALISIS STRATEGI PENERJEMAHAN IDIOM BAHASA PRANCIS DALAM NOVEL L’ÎLE DES PINGOUINS KARYA ANATOLE FRANCE - Hamama, Fathin; Gumilar, Dudung; Widawati, Rika (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2024)
This study aims to analyze idioms in the novel "L'Ile des Pingouins" and their translation strategies in "Hikayat Penguin". Using a descriptive qualitative method, data were collected by selecting idioms from both texts and then analyzed using Fernando’s lexical idiom taxonomy and Baker and Newmark’s translation strategies. The results indicate that semi-idioms, which combine literal and figurative meanings, appear most frequently in the source text. This presents a challenge for translators to find appropriate equivalents in the target language. The analysis found that the paraphrasing strategy is most commonly used, reflecting a tendency to maintain the idiomatic meaning intact by providing a descriptive narration. This study underscores the importance of understanding the cultural and contextual nuances of both languages to achieve accurate and natural translations. Appropriate translation strategies can help preserve the meaning and nuances of idioms from the source language to the target language. These findings contribute to the field of idiom translation studies between French and Indonesian and provide practical guidance for translators in addressing the challenges of idiom translation.